Influência da presença da vegetação na temperatura e na umidade do ar: estudo em bairros da cidade de Cascavel-PR - Otani, Cinthia Thiesen (2019)
The objective of this study was to analyze the green areas of the city of Cascavel/PR, using the calculations of Indexes of Green Areas (IAV/IGA), Green Areas Index of Vegetable Massifs (IAV MV/GAI VM), Percentage of green areas (PAV/PGA) and percentage of green areas of vegetal masons (PAV MV/ PGA VM). All these data were obtained from the 31 neighborhoods of the city in order to obtain the information of the neighborhood with better and worse indexes. Once identified, these neighborhoods were dterminated collection points and data to verify if the urban vegetation influences the climatic variables of air temperature and humidity. Collection points denominated, P1, P2, P3 and P4 were stipulated, with the presence or absence of vegetation of the determined neighborhoods. Região do Lago (Lake Region), which obtained better indexes and Pacaembu, which obtained the worst indexes. With the data collected, it could be observed that the presence of vegetation has great influence in the local microclimate and that the area that has more amount of arboreal mass, have a better climatic conditions on the region of the city that has smaller massive amount of arboreal, in summary.